Economic Transformation In The Digital Era: Opportunities, Challenges And Its Impact On Public Welfare - Nur Laily Hidayati; Zakiyyah Ilma Ahmad; Syafiul Umam; Muhammad Farid Al Azhar (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2026)
The economic transformation in the digital era has transformed various aspects of people's lives through the increasingly widespread use of information and communication technology. This change creates new opportunities for increasing productivity, efficiency, innovation, and expanding access to digital markets and financial services. However, this transformation also presents various challenges, such as the digital divide, low digital literacy, cybersecurity threats, and changing workforce competency requirements. This study aims to analyze the opportunities, challenges, and impacts of the digital economic transformation on public welfare. The method used is library research with a qualitative descriptive approach through the analysis of various scientific sources, such as journals, books, official reports, and relevant publications. The results show that the digital economic transformation contributes positively to improving public welfare through the creation of new jobs, increased income, easier access to economic services, and encouraging the growth of micro, small, and medium enterprises (MSMEs). However, these benefits have not been felt evenly due to gaps in access to technology and digital capabilities. Therefore, synergy is needed between the government, the business world, and the community to improve digital literacy, expand technological infrastructure, and develop inclusive policies so that the digital economic transformation can achieve sustainable public welfare